Prototipe System Absensi Akademik Berbasis Smart Card & Web - Topan, Muhamad; Rari, Excel Fransisco; Wicaksono, Rimulyo (LPPM Universitas Negeri Jakarta, 2019)
List data of students present in class that is important for an academic meeting in the assessment of student activity. The purpose of this research is making the tool